The Students’ Ability in Speaking By Using Duolingo Aplication at Seventh Grade Students of SMP Singosari Delitua - Bukit, Herawati; Pangaribuan, Jontra Jusat; Saragih, Marice (English Lecturers and Teachers Association (ELTA), 2024)
Duolingo is an educational category like playing games, so the students can also use it casually without pressure and also easy to accept and absorb because of flexibility. This research was conducted to determine the ability of the students to speak by using the Duolingo Application. The population of this research was the seventh-grade students of SMP Singosari Delitua. The sample consists of 61 students. This research required two groups of students namely the experimental group and the control group. The experimental group was treated by using the Duolingo application while speaking, whereas the control group was treated without the Duolingo application. The result of this study indicates that the use of Duolingo improves the ability of the students to speak. it can be seen from the deviation of the experimental group and the control group. The mean deviation of the experimental group is 24,07 it means that the deviation is high. This group was taught by using the Duolingo Application Mean of the deviation in control group is 4,87 means that the deviation is low. This group was taught without using Duolingo Application, by using this application made the students understand the material and students were more motivated to learn and brave enough to speak English with the students. Students get the opportunity to get some turn in practicing material in everyday life since the students can practice at home since Duolingo can be accessed anywhere and everywhere, this application reduces boredom in learning English and facilitates remembering and practicing material in a positive attitude towards the application at school. it is also one of the effective media in teaching learning and speaking for the students Key Words: Speaking Ability; Duolingo Application